2015
DOI: 10.1002/art.39174
|View full text |Cite
|
Sign up to set email alerts
|

Down‐Regulation of Rac GTPase‐Activating Protein OCRL1 Causes Aberrant Activation of Rac1 in Osteoarthritis Development

Abstract: Objective. Chondrocyte hypertrophy and mineralization are considered to be important pathologic factors in osteoarthritis (OA). We previously reported that Rac1 was aberrantly activated to promote chondrocyte hypertrophy, mineralization, and expression of matrix metalloproteinase 13 and ADAMTS in OA. However, the underlying mechanism of aberrant Rac1 activation in OA is unclear. The present study was undertaken to identify the specific molecular regulator controlling Rac1 activity in OA, as well as to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…First, we evaluated the knockdown efficiency of Kdm6b shRNA in the murine MSC line C3H10T1/2, and it was shown that the two shRNAs considerably reduced Kdm6b mRNA expression, with Kdm6b-sh2 displaying better efficiency (figure 4A). Then, PLKO and Kdm6b-sh2 were packaged into lentivirus for intra-articular injection of knee joint after DMM surgery, as described previously 11. At the same time, 8-week-old Col2a1-CreER T2 ;Kdm6b f/f mice and Kdm6b f/f littermates were intraperitoneally injected with TM daily for 5 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we evaluated the knockdown efficiency of Kdm6b shRNA in the murine MSC line C3H10T1/2, and it was shown that the two shRNAs considerably reduced Kdm6b mRNA expression, with Kdm6b-sh2 displaying better efficiency (figure 4A). Then, PLKO and Kdm6b-sh2 were packaged into lentivirus for intra-articular injection of knee joint after DMM surgery, as described previously 11. At the same time, 8-week-old Col2a1-CreER T2 ;Kdm6b f/f mice and Kdm6b f/f littermates were intraperitoneally injected with TM daily for 5 days.…”
Section: Resultsmentioning
confidence: 99%
“…Destabilisation of medial meniscus (DMM) surgery was performed on the knee joints of 10-week-old male mice as previously reported 24. We performed intra-articular injection of lentivirus to C57BL/6J wild-type mice after surgical induction according to previously described procedures 11. All animal experiments were approved by the Zhejiang University Ethics Committee (NO.ZJU20160427).…”
Section: Methodsmentioning
confidence: 99%
“…34 Similarly, intra-articular injection of antago-miR would infect not only articular cartilage but also the synovium, which plays an important role in OA development. However, it is technically difficult to identify the role of miR-483-5p in synovium tissue, articular chondrocytes, or other cells in this model.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to lentivirus (GenePharma) injection, 10 mL lentivirus-mediated miR-483-5p (5 0 -AAGACGGGAGAAGAGAAGG GAG-3 0 ) (4 Â 10 8 TU/ml), siTimp2 (5 0 -GGAATGACATCTATGG CAA-3 0 ) (1 Â 10 9 TU/mL), or NC (5 0 -TTCTCCGAACGTGT CACGTTTC-3 0 ), Matn3 (NM_010770.4) (Cyagen Biosciences), TIMP2(NM_011594.3) (Cyagen Biosciences), and corresponding negative controls were injected into the knee joint 34 of male mice (n = 5/group) using a 33G needle and a micro-syringe (Hamilton). For the antago-miR-483-5p injection, 250 mM antago-miR-483-5p (5 0 -CUCCCUUCUCUUCUCCCGUCUU-3 0 ) or antago-mir NC (5 0 -UUGUACUACACAAAAGUACUG-3 0 ) (GenePharma) were injected.…”
Section: Intra-articular Injectionmentioning
confidence: 99%
“…Synovial biopsy shows rubbery tissue without an inflammatory infiltrate and fibrous tissue containing fibrillary material [70]. Zhu et al have recently demonstrated abundant expression of OCRL in normal cartilage, which was downregulated in a mouse model of osteoarthritis and could be restored by intraarticular injection of ORCL -encoding lentivirus [71]. Musculoskeletal complications have not yet been reported in Dent-2 patients.…”
Section: Clinical Manifestations and Managementmentioning
confidence: 99%